2006
DOI: 10.4995/ia.2006.10492
|View full text |Cite
|
Sign up to set email alerts
|

Diseño hidráulico de aliviaderos escalonados en presas de HCR

Abstract: En el presente artículo se presenta un conjunto de criterios para el diseño de aliviaderos escalonados con pendientes típicas de presas de hormigón compactado con rodillo. El texto se basa en Informa­ción recogida en la bibliografía e incorpora los resultados del trabajo de Investigación desarrollado en Amador (2005). Se aborda el diseño de la cresta, la selección del ancho del aliviadero y la geometría de los peldaños. Se proponen criterios para determinar el tipo de flujo existente sobre la estructura y, en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
1
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 13 publications
9
31
1
16
Order By: Relevance
“…Empirical models have been developed for predicting the main air-water flow properties along the chute by Hager and Boes [45], Matos [57], Chanson [25], Boes and Hager [9,10], Meireles [65], Renna [71] and Ohtsu et al [67]. In spite of this considerable number of studies, and to the best of our knowledge, only Amador [2], Amador et al [3], Meireles et al [65], Gonzalez and Chanson [43], Carvalho and Amador [23] and Meireles and Matos [64] have focused on the flow properties of the non-aerated flow region of stepped spillways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical models have been developed for predicting the main air-water flow properties along the chute by Hager and Boes [45], Matos [57], Chanson [25], Boes and Hager [9,10], Meireles [65], Renna [71] and Ohtsu et al [67]. In spite of this considerable number of studies, and to the best of our knowledge, only Amador [2], Amador et al [3], Meireles et al [65], Gonzalez and Chanson [43], Carvalho and Amador [23] and Meireles and Matos [64] have focused on the flow properties of the non-aerated flow region of stepped spillways.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, extensive experimental research has been developed to characterize the flow on conventional stepped spillways for chute slopes typical of either embankment or concrete dams downstream of the inception point of air entrainment, including the assessment of variables such as air concentration and velocity distribution [4,9,24,26,37,42,57,63,67,71] or the pressure field on the steps [2,4,41,74,85]. Empirical models have been developed for predicting the main air-water flow properties along the chute by Hager and Boes [45], Matos [57], Chanson [25], Boes and Hager [9,10], Meireles [65], Renna [71] and Ohtsu et al [67].…”
Section: Introductionmentioning
confidence: 99%
“…A typical evolution of the upper bound of the shear layer in the flow region surrounding step edge 3 is shown in Figure 4 for d c /h = 1.5, where k s = hcos is the step cavity height and L cav is the step cavity length: L cav = (h 2 +l 2 ) 1/2 . The data showed that the shear layer upper bound increased in the longitudinal direction downstream of the step edge and reached a maximum at approximately x/L cav = 0.8, close to the finding of Amador (2005) (Fig. 4).…”
Section: Velocity Distributions In the Developing Flow Regionmentioning
confidence: 51%
“…8 hollow circle symbols). Amador (2005) and Meireles (2011) presented velocity measurements in the developing flow region of skimming flows: the application of the momentum integral equation gave on average f MI  0.08 to 0.12 (Table 2). Both the data of Meireles (2011) and Frizell et al (2013) suggested a larger dimensionless shear stress f MI for the largest step height h (Table 2), although these experiments were conducted for different relative step cavity roughness heights.…”
Section: Boundary Shear Stressmentioning
confidence: 99%
“…The pressures on the steps were analyzed by some authors, such as Sanagiotto (2003), Dai Prá (2004, Amador (2005), Gomes (2006), Conterato (2011), Osmar (2016 and others. Figures 1 and 2 show the mean pressure distribution and the extreme pressure distribution, respectively, on the faces of the spillway stepped according to Sanagiotto (2003) and Osmar (2016).…”
Section: Introductionmentioning
confidence: 99%